1991
DOI: 10.1105/tpc.3.5.517
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Chloroplast mRNA Stability during Leaf Development.

Abstract: During spinach leaf development, chloroplast-encoded mRNAs accumulate to different steady-state levels. Their relative transcription rates alone, however, cannot account for the changes in mRNA amount. In this study, we examined the importance of mRNA stability for the regulation of plastid mRNA accumulation using an in vivo system to measure mRNA decay in intact leaves by inhibiting transcription with actinomycin D. Decay of psbA and rbcL mRNAs was assayed in young and mature leaves. The psbA mRNA half-life w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(90 citation statements)
references
References 43 publications
4
85
1
Order By: Relevance
“…The conclusion that a decrease in polysome recruitment destabilizes the rbcL mRNA may appear to be at odds with the results of Klaff and Gruissem (1991) who found that lincomycin, an antibiotic that decreases the association of chloroplast mRNAs with polysomes, stabilized the rbcL mRNA in spinach leaves. The mutations described here also decrease polysome association of mRNAs, but result in the destabilization of the maize rbcL mRNA.…”
Section: Chloroplast Mrna Metabolismcontrasting
confidence: 52%
See 2 more Smart Citations
“…The conclusion that a decrease in polysome recruitment destabilizes the rbcL mRNA may appear to be at odds with the results of Klaff and Gruissem (1991) who found that lincomycin, an antibiotic that decreases the association of chloroplast mRNAs with polysomes, stabilized the rbcL mRNA in spinach leaves. The mutations described here also decrease polysome association of mRNAs, but result in the destabilization of the maize rbcL mRNA.…”
Section: Chloroplast Mrna Metabolismcontrasting
confidence: 52%
“…A reduction in the elongation rate would, by itself, result in an increase in the number of ribosomes associated with mRNAs, as is observed after treatment of chloroplasts with chloramphenicol (A. Barkan, unpublished results;Klaff and Gruissem, 1991), or eukaryotic cells with cycloheximide (Peltz et al, 1992).…”
Section: Chloroplast Mrnas Are Associated With Abnormally Few Ribosommentioning
confidence: 99%
See 1 more Smart Citation
“…Developmental signals cause changes in plastid transcription, RNA stability, and splicing that occur independently of light (Barkan, 1989; Baumgartner et al, 1993;Kim et al, 1993). In addition, light influences chloroplast gene expression at transcriptional, posttranscriptional, and translational levels (Klein et al, 1988; Berry et al, 1990;Klein and Mullet, 1990;Schrubar et al, 1990;Sexton et al, 1990a;Klaff and Gruissem, 1991; for review, see Gruissem and Tonkyn, 1993;Mullet, 1993;Mayfield et al, 1995). Light activates nuclear genes for plastid ' Portions of this study were supported by funds from the proteins, stimulates the formation of thylakoids, regulates the stoichiometry and turnover of photosynthetic reaction center components, and controls enzyme activity (Melis, 1991;Thompson and White, 1991;Christopher and Mullet, 1994).…”
mentioning
confidence: 99%
“…The lowered levels of the vbcL transcript could be an indirect effect of a decrease in translation, because it has been shown that in spinach this mRNA is highly sensitive to changes in chloroplast translation and processing (Klaff and Gruissem, 1991;Schuster and Gruissem, 1991 (Barkan, 1993). It h a s been suggested that this message, b u t not other chloroplast messages, was destabilized when not associated with ribosomes (Barkan, 1993).…”
Section: Discussionmentioning
confidence: 99%